Smartphone Usage Behavior and Technology Acceptance in Oil Palm Replanting - Yulida, Roza; Andriani, Yulia; Rosnita, Rosnita; Septya, Fanny; Febiola, Ezra; Madiyoh, Abdulhakim (Jurnal AGRISEP, 2024)
Replanting activities need support using information technology so that plantation business actors can access information related to plantations independently and accurately. This research analyzes smartphone usage behavior using a technology acceptance model approach among oil palm users. This research was conducted at the Karya Dharma III Village Unit Cooperative, Keranji Guguh Village, Koto Gasib District, Siak Regency. The sample taken in this research was 30 planters. The sampling technique in this research uses a snowball sampling technique, which is obtained through a rolling process based on the relationship between one respondent and another. Snowball sampling is a sampling method that uses initial illustration data to identify other illustrations that meet the criteria. Data analysis was carried out using a descriptive study based on a Likert scale. The final results of this research show that using smartphones among oil palm planters in Keranji Guguh Village as a medium to help search for and receive information for oil palm planters is classified as moderate, with an average score of 2.84. Smartphone use has become an alternative media planters use to search for information on supporting oil palm rejuvenation activities, land clearing, planting spacing patterns, using superior seeds, and plant maintenance replanting.